Dynamics of an ultra-discrete SIR epidemic model with time delay - Masaki Sekiguchi; Emiko Ishiwata; Yukihiko Nakata (Mathematical Biosciences and Engineering)
We propose an ultra-discretization for an SIR epidemic model with time delay. It is proven that the ultra-discrete model has a threshold property concerning global attractivity of equilibria as shown in differential and difference equation models. We also study an interesting convergence pattern of the solution, which is illustrated in a two-dimensional lattice.